Poziom zasolenia gleb na tle występowania frontu wód słonych infiltrujących ze składowiska odpadów poflotacyjnych "Żazny most" = Saltinity of soils against a background of the occurrence of salty water infiltrating from the tailings impoundment "Żazny most" - Gałka, Bernard; Ochman, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The phenomenon of soil saltinity ? related to getting through to the forelands of over-sediment salty water stored in the tailings impoundment "Iron Bridge" ? was introduced in the paper. Highly-mineralised water infiltrating from the tailing impoundment induce certain consequences for the chemism of the underground and surface water as well as for the water management and properties of soil.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zasolenie; osady poflotacyjne; składowisko odpadów; saltinity; after-flotation wastes; tailing impoundment